FRPRCS-5 fibre-reinforced plastics for reinforced concrete structures - Burgoyne, C. J. (Thomas Telford, 2001)
Fibre reinforced plastics are increasingly being used as replacements for steel reinforcement in concrete structures. The reinforcement can be untensioned or in the form of prestressing tendons. It can also be glued onto the outside of a structure. This title provides up-to-date research results to give engineers confidence in their design methods.